Pre-pregnancy parental BMI and offspring blood pressure in infancy. (29th August 2020) - Jansen, Maria Adriana Cornelia; Dalmeijer, Geertje W; Saldi, Siti RF; Grobbee, Diederick E; Baharuddin, Mohammad; Uiterwaal, Cuno SPM; Idris, Nikmah S
Abstract: Aims: A growing body of evidence suggests that a higher maternal pre-pregnancy body mass index results in higher offspring's blood pressure, but there is inconsistency about the impact of father's body mass index. Furthermore, evidence is limited with regard to low and middle income countries. We aimed to determine the association between parental pre-pregnancy body mass index and offspring's blood pressure during the first year of life. Methods: In 587 infants of the BReastfeeding Attitude and Volume Optimization (BRAVO) trial systolic and diastolic blood pressure were measured twice at the right leg in a supine position, using an automatic oscillometric device at day 7, month 1, 2, 4, 6, 9 and 12. Parental pre-pregnancy body mass index was based on self-reported weight and height. Linear mixed models were performed to investigate the associations between parental pre-pregnancy body mass index and offspring blood pressure patterns. Results: Each unit increase in maternal body mass index was associated with 0.24 mmHg (95% confidence interval 0.05; 0.44) and 0.13 mmHg (0.01; 0.25) higher offspring's mean systolic and diastolic blood pressure, respectively, during the first year of life. A higher offspring blood pressure with increased maternal pre-pregnancy body mass index was seen at birth and remained higher during the first year of life. The association with systolic blood pressure remained similar after including birth size and offspring's weight and height over time. The association with diastolic blood pressure attenuated slightly to a non-significant result after including these variables. Paternal body mass index was not associated with offspring's blood pressure. Conclusion: Higher maternal pre-pregnancy body mass index, but not paternal pre-pregnancy body mass index, is associated with higher offspring blood pressure already from birth onwards.